2015
DOI: 10.4102/phcfm.v7i1.767
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic patients’ perspectives on the challenges of glycaemic control

Abstract: IntroductionThe factors affecting the control of diabetes are complex and varied. However, little is documented in the literature on the overall knowledge of diabetic patients about glycaemic control. This study explored the patients’ perspectives on the challenges of glycaemic control.MethodsIn this qualitative study, semi-structured interviews were conducted with seventeen purposively selected diabetic patients with HBA1c ≥ 9% at Mthatha General Hospital, South Africa. The interviews were conducted in the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Findings relating to how Participants recognised and interpreted their type 2 diabetes were reported in most papers included in the review [ 8 10 , 18 34 ]. A recurring observation was that the symptoms of diabetes were often not recognised by those experiencing them, and healthcare professionals tended to be the first to respond to signs of the disease [ 8 , 21 , 26 , 27 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings relating to how Participants recognised and interpreted their type 2 diabetes were reported in most papers included in the review [ 8 10 , 18 34 ]. A recurring observation was that the symptoms of diabetes were often not recognised by those experiencing them, and healthcare professionals tended to be the first to respond to signs of the disease [ 8 , 21 , 26 , 27 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies found that the majority of people with diabetes understood the links between high sugar diets, inactivity, and obesity as contributors to diabetes. However, there was also evidence that some people with diabetes questioned the links between lifestyle and diabetes, particularly when neither their bodies nor lifestyles reflected dominant narratives which positions type 2 diabetes as a disease of affluence [ 8 , 18 20 , 22 , 25 ]:…”
Section: Resultsmentioning
confidence: 99%
“…This takes off a major financial burden and might have resulted in the observed lack of association between socioeconomic status and HbA 1 C. In contrast, a study from the rural communities of Mthatha, South Africa indicated that poverty and inaccessibility to doctors were the major hurdles faced by patients to attain good glycemic control. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[16] A South African study reported that a major negative factor in glycemic control for the patients from rural communities was a lack of knowledge. [15] It must be remembered that each visit to the clinic is an opportunity to educate the patients on various aspects of diabetes. The group education sessions at our center are a reliable point for sharing, disseminating, and updating knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Blood sugar monitoring is a fundamental part of DM management since it is a parameter for conducting treatment, allowing dose adjustments or changes in drug prescriptions, and determining the physical activity plan and dietary guidelines (ADENIYI et al, 2015). It works as an educational tool, allowing the person evaluating the causes of hypo or hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%